Patogenesis Batu Empedu - Widiastuty, Astri Sri (Syifa'Medika, 2010)
Gallstones are collections of cholesterol, bile pigment or a combination of the two,which are formed in the gallbladder or within the bile ducts. Cholesterol stones primarilycomposed ofcholesterol, while pigmented stones are primarily composed ofbiliru bin.Gallstones formed in the biliary system can cause blockage of the bile ducts andsysmptoms such as abdominal pain, nausea and vomiting, and gallstones can causeinflammation of pancreas (pancreatitis), acute cholecystitis and choledocholithiasis. Riskfactors for developing cholesterol gallstones are female gender, older age, genetic, obesity,high cholesterol level, treatment with estrogen containing medications and liver disease.Gallstones that are not causing symptoms generally do not cause problem and donot require further evaluation. Gallstones are diagnosed by physical examination(murphy's sign), laboratory measurement (ALT, AST, alkaline phosphatase and bilirubin)and radiology procedures abdominal plain x-rays, Ultrasonography, Computedtomography (CT) scan, Magnetic resonance cholangiography (MRCP), Endoscopicultrasound (EUS), and Biliary. scintigrapy.The treatment for gallstones that obstruct the common bile duct is endoscopicretrograde cholangiopancreatography (ERCP) or surgery.